Hydroponic Plant Nutrition Measurements System using Display Smartphone Internet Based of Things - Dwina Melisa; Asrizal, Asrizal; Yulkifli, Yulkifli; Hufri, Hufri; Amir, Harman (Department of Physics, Universitas Negeri Padang, 2024)
Hydroponics is an alternative for people who want to garden, but don't have enough space to grow crops. The most important issue that must be considered in cultivation is the provision of sufficient nutrients for plants. Lack of nutritional value results in less maximum yields. Nutritional measurements can be carried out without having to go to the cultivation site. The purpose of this study was to determine the performance specifications of the nutrient measurement system components for hydroponic plants. Determine the precision and accuracy of the nutrient measurement system on the results of limited-scale tests and field-scale test results. This type of research is engineering research. The data analysis technique used is descriptive data analysis and error analysis. From the data analysis it can be stated that three research results are first, the specification of system components includes sensor performance, ESP8266, LCD, Blynk. Second, the precision of the average nutrition on a limited scale is 99.97% and the average accuracy is 99.14%. Third, precision of nutrition on a field scale is 99.47% and the average accuracy is 99.14%. Field-scale test results were carried out for 3 days to obtain varied data. For cultivators of hydroponic plants it is useful for measuring nutritional value so they no longer make measurements manually.